Enhancing English Listening Skills: A Case Study of the CAKE Application in Student Learning - Aldilla Rozias Eka Putri; Deasy Yunita Siregar (Green Publisher Indonesia, 2024)
In today's world of education, mastery of English is important for students all over the world, including in Indonesia. Despite its importance, many learners struggle with English language proficiency, particularly in listening comprehension. This research explores the effectiveness of the CAKE application in improving English listening skills among secondary school students in North Sumatra, Indonesia. Using qualitative case study methodology, data was collected from 10 participants through interviews and observations. Findings showed significant improvements in students' listening skills after using the CAKE app, as evidenced by their performance in listening tests and self-reported experiences. Participants reported improvements in the quality of English such as better vocabulary and listening skills than before, increased self-confidence, focus and motivation in learning English, and this was due to the interesting features of the application. Although there were some challenges, such as selecting videos and understanding unclear audio, students provided valuable suggestions to improve the app's effectiveness. Overall, the CAKE app offers a promising solution for improving English listening skills, providing students with an accessible and engaging platform for language learning outside the classroom. By meeting students' needs and incorporating their input, CAKE applications have the potential to further improve language learning outcomes and contribute to students' overall language proficiency in a globalized world.